Reduksi Otonomi Seluas-Luasnya Dalam Undang-undang Nomor 32 Tahun 2004 tentang Pemerintahan Daerah - ACHMAD AZIS (Fakultas Hukum Universitas Mulawarman, 2008)
Article 18 in Amandement of Indonesia’s Constitution (UUD 1945) recognizes authority of localgovernment by which it regulates it’s authority by self government, that was regulated inConstitution. Article 18 section (5) of Indonesia’s Constitution explained that local government canapply it’s autonomy to regulate authories in line with the Constitution except those remarked asthe authorities of central government. Meanwhile, Act of 32 of 2004 applied principle of autonomyof local goverment that has reducted. Based on this explanation, the aim of this research is the firstattempt to analyze principle of autonomy of local goverment in Constitution and secondly toanalyze the implimentation of local government authority according to Act of 32 of 2004. Thisresearch applies an inquiry of analytical jurisprudence paradigm. This methode has appliedto research “the existing national law in its day to day practice, and the law in action” of eachsystem, therefore this is explanatoris and analysis research.Key words: otonomi (autonomy), pemerintahan daerah (local government)